Association of Excess Dietary Iodine Intake with Papillary Thyroid Carcinoma (Bangladesh Journal of Nuclear Medicine, 2023)
Background: Papillary thyroid carcinoma (PTC) is the most common type of differentiated thyroid carcinoma and accounts for 70–80% of all thyroid carcinomas. After the global iodine fortification of salt and food, the incidence of PTC has been increasing throughout the world in recent years.Aims: To determine the relationship between excessive dietary iodine intake and PTC.Patients and methods: This cross-sectional study was carried out at the National Institute of Nuclear Medicine & Allied Sciences (NINMAS), Dhaka, from March 2020 to June 2021. A total of 111 patients were included in this study, of whom 53 were pre-operative papillary thyroid carcinoma patients and the rest, 58, were age- and sex-matched healthy individuals. Their urinary iodine concentrations were measured in the laboratory of the Bangladesh Reference Institute for Chemical Measurements (BRICM). Urinary iodine concentration is a good marker of dietary iodine intake. Statistical analysis of the results was obtained using Windows-based computer software devised with Statistical Packages for Social Sciences (SPSS) version 23.0.Results: The mean urinary iodine concentration was 223.54±55.78 microgram/liter in the PTC group and 154.29±61.83 microgram/liter in the healthy group. A remarkable number of participants in both the PTC group 42 out of 53 (79.3%) and the healthy group 18 out of 58 (31.0%) had biochemical evidence of excess iodine intake. Excess iodine intake significantly (p